How Principal Strategies in Developing Teacher Professional Competence Improve Educational Quality: A Systematic Review - Rahman, Arief; Yuliani, Helda (Jurnal Hadratul Madaniyah, 2025)
Improving the quality of education hinges significantly on the leadership strategies of school principals, especially in the systematic development of teacher professional competence. This systematic review explores the strategic approaches employed by school principals to foster teacher professional competence and, consequently, improve educational quality. Employing a qualitative Systematic Literature Review (SLR) guided by PRISMA standards, this study synthesizes research published between 2020–2025, emphasizing frameworks such as TCCM and best practices in educational leadership. The findings reveal principal strategies that integrate instructional leadership, collaborative professional development, data-driven decision-making, inclusive school culture, and adaptive change management. Challenges persist, including resource constraints, varying teacher motivation, and policy-practice misalignments, but successful strategies hinge on collaborative environments, targeted professional development, continuous evaluation, and fostering a culture of innovation and resilience. The review provides robust theoretical and practical recommendations for policymakers, educational leaders, and practitioner communities seeking to elevate educational outcomes via strategic principal leadership in teacher competency development.